Crucifixian fact or fiction - Deedat, Ahmed; Douglas, Robert; Saba Islamic Media ([Kuala Lumpur] : Saba Islamic Media)
A debate between Sheikh Ahmed Deedat and Dr. Robert Douglas on the topic of the crufixion. Held at University of Kansas, USA on 6th November 1986
Title from title screen
Speakers: Sheikh Ahmed Deedat, Dr. Robert Douglas
DVD Format
Keywords: Jesus Christ -- Crucifixion; Jesus Christ